Internet Language Features on Male and Female Music Video Commentators in YouTube: A Sociolinguistics Study - Moch. Haydar Yahya; Bambang Yulianto; Elisa Nurul Laili (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2021)
Internet becomes one vital need for human because it is used for communicating with others and getting the information needed. The existence of internet cannot be separated from the role of advancement and technological sophistication. The rising need for internet has an impact on languages Danet (2001) provides an explanation of the language used in the Internet world. He states there are ten Internet Language Features; Multiple punctuation, Eccentric spelling, Capital letters, Asterisks for emphasis, Written-out laughter, Music/noise, Descriptions of actions, Emoticons, Abbreviations, and Rebus writing. This study aims to use Internet Language Features by Danet (2001) on social media users of YouTube both male and female applied in commenting on Bad Guy's Music Video by Billie Eilish. This research uses a qualitative approach and descriptive method. The results of this study indicate that both male and female commentators alike use nine out of ten internet language features. Only one feature is not used, it is the Asterisks which usually used for emphasizing feature.